Translation Through The Lens Of Linguistic Norms: A Comprehensive Study - Kasimova Nafisa Farhadovna (Genius Journals, 2024)
This article examines the essence and role of linguistic norms in translation, emphasizing their importance in maintaining the stability and adaptability of literary languages. It explores the dual nature of norms as both descriptive and prescriptive, highlighting their conservative yet dynamic characteristics. The discussion includes the differentiation between various language norms, such as territorial, functional, and stylistic, and their impact on translation practices. The article underscores the necessity for translators to master both source and target text norms to achieve adequate translations, considering the structural and cultural nuances of each language. This comprehensive analysis underscores linguistic norms as pivotal in ensuring translational fidelity and coherence.
Keywords: linguistic norms; translation; literary language; normativity